Incidence and epidemiological features of synchronous and metachronous colorectal cancer - Brambilla,Eduardo (2013)
INTRODUCTION: patients with sporadic colorectal cancer or cases associated with syndromes are at risk of having synchronous or metachronous cancer. Although it is an important subject, Brazilian data on the subject are scarce. OBJECTIVE: to evaluate the incidence and epidemiological features in patients with synchronous and metachronous colorectal cancer in a reference service of proctology in the Rio Grande do Sul. Methods: cross-sectional observational study, performed between January and July 2012, analyzing all patients admitted in the service that met the inclusion criteria. A retrospective review of records was performed, noting demographic variables, comorbidities and tumor-related variables. RESULTS: 150 records were analyzed, of which 53.3% were males and mean age was 63 (± 13.01) years old. The most frequently found tumor location was the sigmoid colon and high rectum (50.67%), followed by the lower rectum (36%). Adenocarcinomas were the most prevalent histological subtype (88%), followed by epidermoid tumors (1.33%). Hereditary syndromes were identified in five patients (3.33%), with four being Familial adenomatous polyposis (FAP) and one hereditary nonpolyposis colorectal cancer (HNPCC). Among the analyzed patients, four (2.67%) had synchronous and one (0.67%) had metachronous cancer. CONCLUSION: the incidence of synchronous and metachronous colorectal cancer was, respectively, 2.67% and 0.67%, results that corroborate those reported in international literature.